Lifetime consumption and degradation analysis of the winding insulation of electrical machines - Sciascera, C; Galea, Michael; Giangrande, Paolo; Gerada, C. (2016)
In this paper, a novel multi-stress model which estimates the lifetime of the winding insulation relative to its duty cycle is proposed and investigated. With an adequate implementation of this model, then an electrical machine can be designed not only in terms of its performance requirements, but also considering the associated reliability and lifetime aspects. Since thermal and thermo-mechanical stresses are considered as the main ageing factors, the model is particularly suited for low voltage, low duty cycle machines. The determination of the model parameters is based on the results of accelerated thermo-mechanical ageing tests, whose procedure is thoroughly reported in the paper. The results of the accelerated ageing tests show that the effect of thermo-mechanical ageing is significant even for small size, random wound windings under fast temperature rise.